Propriétés stylistiques de l’auto-sociobiographie : l’exemplification par l’écriture d’Annie Ernaux - Bérengère Moricheau-Airaud (Contextes)
As they fall social matters within and through the style, Annie Ernaux’s texts differentiate themselves from the thought of relationship between sociology and literature by falling under a straight transparency between a text and its context: they shape, even symbolize, exemplify the combination of both sociocritics and sociodiscursives dimensions. The stylistic properties in which the conversion of an intimist life to a social reality hatches indeed implement an exemplification of a personal reality into a group one, and thus engage the auto-sociobiography reality. Annie Ernaux’s writings are de facto underpinned by a rhetoric of the example: their characters are made of typical representations of the relationship to social matters; these representations are even exemplified, in other words increased by a symbolic value at which the text openly refers to; the argumentative and political concerns vested in the representations offer them as exempla to the sociological postulates. These auto-sociobiography characters induce the work of dynamics that transforms the reality of one life into a common reality: Annie Ernaux’s writing is a place of tensions, between social and literature realities, between conjecture and exemplified realities; the leap from one plan to another induces a distancing search from the intimate; the autobiographic pact is thus remodeled. These transformations determine a writing socialization, in the collectivization of enunciation marks, in the extension of the references and in the structures unspecialization. These are all stylistic special features of auto-sociobiography, gathered as studied by the critics, and as given by the author.